Review article of microwave imaging techniques and dielectric properties for lung tumor detection - Siti Nuranis, Muhammad; Muammar, Mohamad Isa; Faizal, Jamlos (AIP Publishing, 2020)
This article presents the microwave imaging techniques in order to detect early lung cancer with dielectric properties of normal and cancerous tissues which affect the propagation of the microwave signal. Identifying the contrast of dielectric properties of normal and cancerous lung tissues is significant in microwave imaging because it is used in reconstructing the image either in radar-based or tomographic imaging techniques. In microwave imaging measurement from past researchers are highlighted in order to identify the optimum distance of the antenna from the human thorax and the significant size of the tumour that can be detectable.